Prenatal heating effects of ultrasound: a review - Radzi,, Nadzirah Mohamad; Ahmad Zaiki, Farah Wahida (Faculty of Medicine and Health Sciences, 2018)
The application of ultrasound technology has been widely accepted in clinical settings, particularly in Obstetrics and Gynaecology. This is in light of its ability to detect early foetal malformations apart from enabling foetal monitoring throughout gestation. While ultrasonography is an imaging method that is regularly used in Obstetrics, it is questionable as to whether it is safe for foetuses. The purpose of this paper was to review the evidence regarding the thermal effects of ultrasound exposure on foetal development, particularly. It is hoped that the importance of prudent usage of prenatal ultrasonography will be impressed on clinicians and the public in order to avoid the unnecessary usage of ultrasonography when it is not medically indicated. This is so that the welfare of pregnant women will be looked after, besides contributing to the better health of the next generation by ensuring that the benefits outweigh the known risks or potential harms. © 2018 Faculty of Medicine and Health Sciences.